The association of autoimmune thyroid disease (AITD) with psoriatic disease: a prospective cohort study, systematic review and meta-analysis. Issue 4 (October 2017) - Khan, Samer R; Bano, Arjola; Wakkee, Marlies; Korevaar, Tim I M; Franco, Oscar H; Nijsten, Tamar E C; Peeters, Robin P; Chaker, Layal
Abstract : Objective: Autoimmune thyroid disease (AITD) and psoriatic disease share auto-immunological components. Few studies have investigated the link between both, yielding inconclusive results. Design: We assessed the association of AITD with psoriatic disease in a prospective cohort study and performed a systematic review and meta-analysis. Methods: 8214 participants of the Rotterdam Study (RS) with thyroid peroxidase antibodies (TPO-Abs), thyroid-stimulating hormone (TSH) and/or free thyroxine (FT4) measurements and information on psoriatic disease were included. We performed logistic and Cox regression analyses and a systematic literature search in several electronic databases on AITD and psoriatic disease. We pooled odds ratios (ORs) of included studies using the Mantel-Haenszel method, while adding RS data on prevalent psoriatic disease. Results: Within the RS, we found no association between TPO-Ab positivity and psoriatic disease. There was a positive trend between TSH and prevalent psoriatic disease, and between FT4 and incident psoriatic disease, although not significant. Out of 1850 articles identified, seven were included in the systematic review and four in the meta-analysis. The risk of psoriatic disease (pooled OR) was 1.71 (confidence interval (CI): 1.27–2.31) for TPO-Ab positivity, 1.25 (CI: 1.14–1.37) for AITD and 1.34 (CI: 1.16–1.54) respectively, and 1.17 (CI: 1.03–1.32) for hypothyroidism and hyperthyroidism. Conclusions: Our meta-analysis suggests that TPO-Ab positivity, hypothyroidism and hyperthyroidism might be associated with prevalent psoriatic disease. However, there are only few studies with large heterogeneity regarding psoriatic disease definition and indication of publication bias. Additional prospective data are needed to assess the association of AITD with incident psoriatic disease.